“Ganti Presiden Jangan Sampai Ganti Program”: Critical Discourse Analysis of the Teun Van A Dijk Model - Catur Priyo Putranto (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The purpose of this research is to reveal the ideology implied in the discourse by Kompas.com using Teun A. Van Dijk’s critical discourse analysis theory. The presidential election that is routinely held every four years in Indonesia is a big event for all Indonesian people. Therefore, at this time the media has begun to report news about the strategies of various political parties. So it is necessary to do a more in-depth analysis of the news text presented. This research is a descriptive qualitative research using Teun A. Van Dijk’s discourse analysis theory as the analysis tool. This research selected two news articles with the topic of PDI-P party plans and President Joko Widodo and his Volunteers towards the 2024 Presidential General Election published by Kompas.com. After the analysis, it was found that in the news about the plans of PDI-P and President Joko Widodo regarding the General Election in 2024 Kompas.com always favored PDI-P or President Joko Widodo.